Patient-generated health communication: a novel readability analysis of online reviews in orthopaedic surgery - Shroat, Delaney G.; Goetz, James R.; Major, Edward L.; Carroll, Amber N.; Nash, James D.; Badarudeen, Sameer (International Journal of Research in Orthopaedics, 2025)
Background: Health literacy plays a critical role in patient outcomes, treatment adherence, and care satisfaction. Leading national health organizations and institutions recommend that health communication materials be written at or below the sixth-grade reading level to maximize accessibility. However, the appropriateness of this standard for digitally engaged patient populations remains unclear. This study examined the readability of patient-written online reviews of orthopaedic surgeons to explore whether higher readability levels may still support effective patient communication. Methods: Orthopaedic surgeons were randomly selected from the American Association of Hip and Knee Surgeons (AAHKS) directory. The most recent online patient review (minimum 50 words) for each surgeon was retrieved from Healthgrades.com, along with the surgeon’s star rating and reviewer’s ZIP code. Readability was assessed using validated tools, including the Flesch-Kincaid grade level (FKGL). Statistical analyses were performed to explore the relationships between readability scores and surgeon rating, geographic region, and household income. Results: A total of 114 reviews and ratings were analyzed. The mean FKGL was 7.46 (SD 2.49; median: 7.24), significantly above the sixth-grade recommendation (t (114) =6.251, p<0.001). No significant associations were found between the readability level and star rating (p=0.976), region (p=0.697), or median income (p=0.720). Conclusions: These results suggest that patients actively participating in online health communication exhibit higher literacy levels than the current guidelines assume. This suggests that health communication materials can be crafted at a higher readability level, potentially enhancing message clarity, engagement, and educational value without reducing patient comprehension.